PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) MENGENAI DESTINASI WISATA DOMESTIK PADA MEDIA SOSIAL TIKTOK @TIKETCOM TERHADAP MINAT BERKUNJUNG FOLLOWERS - Luffi Hanifah (2023)
ABSTRACT The presence of the Covid-19 pandemic since 2020 has caused a fluctuating pattern of tourist movements, necessitating marketing activities. One of these activities is the use of electronic word of mouth (eWOM), which can serve as a marketing solution. eWOM can be found on social media platforms such as TikTok, where Online Travel Agency (OTA) Tiket.com utilizes it to market its content related to domestic tourist destinations. This study aims to determine the effect of electronic word of mouth (eWOM) on the interest of TikTok followers in visiting domestic tourist destinations, using the Word of Mouth theory and the eWOM concept. The study employs an explanatory quantitative method with purposive sampling techniques, and descriptive data analysis techniques, classical assumption tests, correlation tests, linear regression tests, coefficient of determination tests, and hypothesis T tests. The results reveal a very strong positive relationship of 0.829 between eWOM and interest in visiting. This implies that if the credibility, quality, and quantity indicators on the eWOM dimension improve, the indicators of interest in visiting, namely transactional, referential, preferential, and explorative interest, will also improve. Through calculations, it is determined that electronic word of mouth (eWOM) has a 68.7% influence on interest in visiting, while the remaining 31.3% is influenced by other unexamined variables. The hypothesis test results indicate that H0 is rejected, and H1 is accepted, leading to the conclusion that there is a significant influence of eWOM on the interest of TikTok followers regarding domestic tourist destinations on the @tiketcom account.